The Relations of News Exposure About Effectiveness of Various Vaccines and Word of Mouth With Level of Public Trust on Covid-19 Vaccines - Thalya Anggita Putri; Triyono Lukmantoro; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The Covid-19 vaccination program in Indonesia has been started since early 2021. Effectiveness, side effects, and the level of public awareness are still a problem in achieving the predetermined Covid-19 vaccination target. This study was conducted with the aim of knowing the relationship between news exposure on the effectiveness of various vaccines and word of mouth with the level of public trust on Covid-19 vaccination. The theory used in this study is the New Media Theory and Theory of Reasoned Action (TRA) with a non-probability sampling technique, totaling 50 samples with characteristics male and female, aged 18-25 years old, living in Pekalongan , and have seen, read, and heard news about the effectiveness of various Covid19 vaccines. This research hypothesis testing using Kendall’s Tau B analysis technique shows a positive result or there is a relationship between exposure to news on the effectiveness of various vaccines and word of mouth with the level of public trust on Covid-19 vaccination with a significance value on both hypothesis tests of 0.000 which means it is very significant. The recommendation of this research is institutions and governments that handle news about Covid19 can publish more positive news about Covid-19 vaccinations and immediately clarified negative news that exist in order to increase the public trust on taking Covid-19 Vaccination.